2023
DOI: 10.3389/fphys.2023.1079503
|View full text |Cite
|
Sign up to set email alerts
|

A fully-mapped and energy-efficient FPGA accelerator for dual-function AI-based analysis of ECG

Abstract: In this paper, a fully-mapped field programmable gate array (FPGA) accelerator is proposed for artificial intelligence (AI)-based analysis of electrocardiogram (ECG). It consists of a fully-mapped 1-D convolutional neural network (CNN) and a fully-mapped heart rate estimator, which constitute a complementary dual-function analysis. The fully-mapped design projects each layer of the 1-D CNN to a hardware module on an Intel Cyclone V FPGA, and a virtual flatten layer is proposed to effectively bridge the feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated the successful implementation of CNNs on FPGAs, achieving high accuracy in real-time patient monitoring systems. RNNs and LSTMs extend this capability by processing the temporal characteristics of ECG signals, where the sequence and timing of heartbeats provide insights into cardiac rhythm and identify abnormalities [17] [19]. Furthermore, the integration of FP-GAs in ECG signal analysis has facilitated the development of modern implantable cardiac devices such as pacemakers, where their high-performance and energy-efficient characteristics are crucial [20].…”
Section: Motivationmentioning
confidence: 99%
“…Studies have demonstrated the successful implementation of CNNs on FPGAs, achieving high accuracy in real-time patient monitoring systems. RNNs and LSTMs extend this capability by processing the temporal characteristics of ECG signals, where the sequence and timing of heartbeats provide insights into cardiac rhythm and identify abnormalities [17] [19]. Furthermore, the integration of FP-GAs in ECG signal analysis has facilitated the development of modern implantable cardiac devices such as pacemakers, where their high-performance and energy-efficient characteristics are crucial [20].…”
Section: Motivationmentioning
confidence: 99%
“…Hardware acceleration significantly impacts disease detection techniques in several ways, providing faster processing, improved accuracy, deployment of real-time applications, scalability, and edge computing. An FPGA accelerator is proposed for an AI-based analysis with an electrocardiogram signal to monitor the heart condition [31]. A onedimensional convolutional neural network has been implemented using the hardware accelerator.…”
Section: Literature Reviewmentioning
confidence: 99%